MODEL EVALUASI PROGRAM PENDIDIKAN KARAKTER DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI - Rismiyati Nurindarwati; Mulyoto Mulyoto; A. Dardiri Hasyim (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2022)
The study aimed at describing the achievement of evaluation model of character education program in learning Islamic Religion and Attitude subject, in implementing teaching learning activity, extracurricular and implementing character education program in SMP Negeri 1 Surakarta. The study used CIPP (Contest, Input, Process, and Product) model as means to conduct evaluation. The approach used in this study was descriptive. The data were collected during evaluation process were by interview, observation, document and questionaire. The data were analyzed by using data reduction, data presentation, and drawing conclusion. The data sources were headmaster, committee, Islamic Religion teachers, students’ parents, and students of VIII and IX year. Result of the study showed that character education program in learning Islamic Religion and Attitude subject have achieved good result implemented by the school holder. On the stage of context, the mean achievement was 88.33% belonging to effective category. On the stage of input, it has achieved 91.78% belonging to effective category. On the stage of process, it has achieved 87.60% belonging to effective category. Finally, the stage of product showed the mean of 90.04% belonging to effective category.